Utilization of PARCS/Serpent in small-scale reactor – Multiplication factor, rod worth, and transient. (February 2022) - Fejt, F.; Suk, P.; Frybort, J.; Rataj, J.
Highlights: Methods and results are verified on 7 different core configurations. Cross-section homogenization based on different approaches. Analyses of a general cross-section library at VR-1 for deterministic codes. Analyses of general core kinetics parameters at VR-1. Steady-state and transient experiments to support the calculation results. Abstract: The paper is focused on utilization of calculation code PARCS (version 3.3.1) for the VR-1 reactor. Macroscopic cross-sections are generated by stochastic code Serpent (version 2.1.30) with ENDF/B-VIII.0 library and with a high emphasis on a wide range of utilization and reproducibility. The VR-1 reactor is characterized by small-sized core configurations (28.6 × 28.6 cm up to 42.9 × 42.9 cm; height of 60 cm; pitch 7.15 cm) that are imposing special requirements on a cross-section homogenization. Published cross-section generation approaches are used for analyses of 7 highly distinctive core configurations. This allows to asses their performance in a wider range than other papers aiming only at one specific core configuration. Even though predictions of a critical state are not sufficiently accurate for any actual usage (in case of the VR-1 reactor), calculated absorption rod worths reach a high potential for a fast and precise evaluation of safety criteria. Core kinetics parameters generated by Serpent with ENDF/B-VIII.0 library (for all three methods: Meulekamp, Nauchi, IFP) show a continuous underestimation of calculated power in all investigated transients during an insertion of a negative reactivity.